2007
DOI: 10.1128/aem.01758-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Reporter Assay and Immunomagnetic Separation Real-Time Reverse Transcription-PCR for the Detection of Enteroviruses in Seeded Environmental Water Samples

Abstract: Two newly developed protocols for infective virus detection were compared to the plaque assay. An immunomagnetic separation procedure coupled with real-time reverse transcription-PCR of viral nucleic acids was developed to identify intact enteroviral particles, and a reporter cell system responding to viral replication based on fluorescent resonance energy transfer for detection of infectious enteroviruses was tested. Both new procedures detected infective viruses in environmental samples at the same level as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Bead-virus complexes can be magnetically separated from the sample and washed to yield concentrated and purified viral particles. Immunomagnetic separation has been used to achieve sensitive detection of EV, RV, HAV and NoV from water, lettuce, green onions, strawberries, shellfish and sewage (Abd el- Galil et al 2005;Arnal et al 1999;Bidawid et al 2000;Casas and Sunen 2002;Gilpatrick et al 2000;Grinde et al 1995;Hwang et al 2007;Jothikumar et al 1998;Kobayashi et al 2004;Lopez-Sabater et al 1997;Monceyron and Grinde 1994;Myrmel et al 2000;Park et al 2008;Shan et al 2005;Sunen and Sobsey 1999). One pitfall of immunomagnetic separation for enteric viruses is that the antibody reagents may be too specific, failing to capture all possible strains of a target virus.…”
Section: Sample Preparationmentioning
confidence: 98%
“…Bead-virus complexes can be magnetically separated from the sample and washed to yield concentrated and purified viral particles. Immunomagnetic separation has been used to achieve sensitive detection of EV, RV, HAV and NoV from water, lettuce, green onions, strawberries, shellfish and sewage (Abd el- Galil et al 2005;Arnal et al 1999;Bidawid et al 2000;Casas and Sunen 2002;Gilpatrick et al 2000;Grinde et al 1995;Hwang et al 2007;Jothikumar et al 1998;Kobayashi et al 2004;Lopez-Sabater et al 1997;Monceyron and Grinde 1994;Myrmel et al 2000;Park et al 2008;Shan et al 2005;Sunen and Sobsey 1999). One pitfall of immunomagnetic separation for enteric viruses is that the antibody reagents may be too specific, failing to capture all possible strains of a target virus.…”
Section: Sample Preparationmentioning
confidence: 98%
“…Since a "gold standard" for the detection of viruses in environmental samples is not yet defined, the prevalence of viral contamination might be underestimated by our methods (15,16,26). Furthermore, it was shown that the number of samples taken at one site influenced the probability of virus detection, also suggesting more drinking water sources in danger of viral contamination.…”
Section: Discussionmentioning
confidence: 99%
“…In numerous studies, virus concentration from water was achieved by filtration using electropositive filters (1MDS) (12,15,25,26,33). Further methods using ultrafiltration, glass wool filters (7,22), or immunomagnetic separation (16,28) were used to detect small amounts of viruses independently of matrix effects. However, the U.S. Environmental Protection Agency listed adenovirus as one of nine microorganisms on the contamination candidate list for drinking water as a potential indicator virus due to an outstanding resistance to UV disinfection.…”
mentioning
confidence: 99%
“…An effective concentration of samples is necessary to evaluate virological quality of wastewaters, since matrices are highly contaminated with inhibitory substances that will interfere with viral detection [11]. Numerous methods have been described for concentrating and extracting enteric viruses from sewage [14][15][16]. All of them studied on spiked viral particles in decontaminated samples.…”
Section: Introductionmentioning
confidence: 99%